Buddhism and Martial Arts in Premodern Japan: New Observations from a Religious Historical Perspective - Trenson, Steven (Religions, 2022)
This article investigates two issues regarding the Buddhism of premodern Japanese martial arts. The first issue concerns the historical channels through which Buddhist elements were adopted into martial lineages, and the second pertains to the general character of the Buddhism that can be found in the various martial art initiation documents (densho). As for the first issue, while previous scholarship underscored Shugendō (mountain asceticism) as an important factor in the earliest phases of the integration process of Buddhist elements in martial schools, this study focuses on textual evidence that points to what is referred to as "medieval Shinto"—a Shinto tradition that heavily relied on Esoteric Buddhist (Mikkyō) teachings—in scholarship. Regarding the second issue, although numerous studies have already shown the indebtedness of premodern martial schools to Buddhist teachings drawn mainly from the Esoteric Buddhist or Zen traditions, this article sheds more light on the nature of these teachings by drawing attention to the fact that they often emphasize the Buddhist thought of isshin or "One Mind". The article illustrates how this thought was adopted in premodern martial art texts and in doing so clarifies the reasons why Buddhism was valued in those arts.